(untitled) (Comparative & International Education Series, 2021)
Aimed at faculty and administrators, this chapter describes viable and accessible virtual strategic initiatives that Historically Black Colleges and Universities can adopt to advance internationalization in general, and global learning in particular. It frames these opportunities in terms of the circumstances precipitated by the coronavirus pandemic. By citing current virtual projects on college and university campuses, it demonstrates that HBCUs can exploit the greater credibility and visibility that virtual learning has recently acquired to launch affordable global learning opportunities for their students that can help prepare them to be globally competent and that can last well beyond the end of the pandemic.